A typology of purpose clauses - Schmidtke-Bode, Karsten (Typological studies in language, 2009)
This book presents the first comprehensive typology of purpose clause constructions in the world's languages. Based on a stratified variety sample of 80 languages, it uncovers the unity and diversity of the morphosyntactic means by which purposive relations are coded, and discusses the status of purpose clauses in the syntactic and conceptual space of complex sentences. Explanations for significantly recurrent coding patterns are couched in a usage-based approach to language structure, which pays due attention to the cognitive and communicative pressures on usage events involving purpose claus.